Hyponatremia caused by excessive intake of water as a form of child abuse - Min A Joo; Eun Young Kim (Korean Society of Pediatric Endocrinology, 2013)
Hyponatremia is the most common electrolyte disorder that requires careful management. Water intoxication with hyponatremia is rare condition that originated from overhydration. Water intoxication, also known as dilutional hyponatremia, develops only because the intake of water exceeds the kidney's ability to eliminate water. Causes of this water intoxication include psychiatric disorder, forced water intake as a form of child abuse and iatrogenic infusion of excessive hypotonic fluid. We experienced and reported a case of symptomatic hyponatremia by forced water intake as a form of child abuse.